Inhibition of the recBCD-dependent activation of Chi recombinational hot spots in SOS-induced cells of Escherichia coli. - Rinken, R (1992)
Nucleotide sequences called Chi (5'-GCTGGTGG-3') enhance homologous recombination near their location by the RecBCD enzyme in Escherichia coli (Chi activation). A partial inhibition of Chi activation measured in lambda red gam mutant crosses was observed after treatment of wild-type cells with DNA-damaging agents including UV, mitomycin, and nalidixic acid. Inhibition of Chi activation was not accompanied by an overall decrease of recombination. A lexA3 mutation which blocks induction of the SOS system prevented the inhibition of Chi activation, indicating that an SOS function could be responsible for the inhibition. Overproduction of the RecD subunit of the RecBCD enzyme from a multicopy plasmid carrying the recD gene prevented the induced inhibition of Chi activation, whereas overproduction of RecB or RecC subunits did not. It is proposed that in SOS-induced cells the RecBCD enzyme is modified into a Chi-independent recombination enzyme, with the RecD subunit being the regulatory switch key.